MERANCANG SISTEM INFORMASI PENJUALAN BERBASIS WEB DI USAHA KECIL DAN MENENGAH - Ahmad, Mubarik (Jurnal Nasional Teknologi Komputer, 2022)
The aim of this research is to create a web-based information system design for small and medium enterprises (SMEs) to help them facilitate their technology business. This research was conducted using a qualitative descriptive method with a literature review based on various studies that have been conducted and using object-oriented approaches such as system builder, development methods, etc. which were developed using the prototype method. The results obtained from this study are the design of information systems that can facilitate SMEs in sales and promotions. The conclusion is that a website information system can help small and medium businesses to develop their business in terms of promotion and sales so they can compete with big companies. Information systems capacity can create new opportunities for small and medium enterprises to expand their market share at a reasonable cost.